China's Growth and Poverty Reduction : Trends between 1990 and 1999 - Chen, Shaohua; Wang, Yan (World Bank, Washington, DC, 2014)
The authors investigate recent rends in poverty, and inequality in China, decomposing data on poverty reduction to see who has benefited most from China's economic growth. They find that, by several measures, poverty declined significantly in the 1990s, across a wide range of poverty lines, except that a slight slowdown in China's export, and economic growth in 1997-99 might have hurt the poor. There was a slight increase in the poverty headcount between 1997 and 1999, using lower poverty lines, and a worsening of the poverty gap index. Average per capita consumption declined for farmers, especially those living in poor regions such as Gans, Heilongjiang, Sanxi, and Xinjiang. It is unclear whether this decline was attributable to Asia's economic crisis. Economic growth contributed significantly to poverty reduction, but rising inequality worsened both rural, and urban income distributions - except during the Asian crisis, when the distribution remained relatively stable. The poor benefited far less than the rich from economic growth. Income growth reached, or exceeded the average growth rate only for the richest twenty percent of the population. The authors then examine the relationship between human capital, growth, and poverty. They find that the accumulation of human capital had slowed, and that there is a huge regional disparity in human capital stock. And the distribution of education is becoming increasingly skewed. China must address this problem if it is to succeed in attacking poverty, and inequality.